2018
DOI: 10.1101/241406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acoustically Targeted Chemogenetics for Noninvasive Control of Neural Circuits

Abstract: Neurological and psychiatric diseases often involve the dysfunction of specific neural circuits in particular regions of the brain. Existing treatments, including drugs and implantable brain stimulators, aim to modulate the activity of these circuits, but are typically not cell type-specific, lack spatial targeting or require invasive procedures. Here, we introduce an approach to modulating neural circuits noninvasively with spatial, cell-type and temporal specificity. This approach, called acoustically target… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…As a noninvasive technique capable of targeting viral vectors to a specific region of the brain, FUS-BBBO creates an unprecedented opportunity for noninvasive control of neural activity with spatial, temporal, and cell-type specificity. These aspects were recently combined in a technique called acoustically targeted chemogenetics (ATAC) (115), which uses FUS-BBBO to deliver viral vectors to specific brain regions, using cell-specific promoters to target selected populations of cells within those regions and encoding chemogenetic receptors—proteins that respond exclusively to bioinert drugs (116)—to gain temporal control of the targeted cells. ATAC holds significant advantages over typical neuropsychiatric drugs, which act indiscriminately throughout the brain with limited regional and cellular specificity.…”
Section: Ultrasound-assisted Biomolecular Transportmentioning
confidence: 99%
“…As a noninvasive technique capable of targeting viral vectors to a specific region of the brain, FUS-BBBO creates an unprecedented opportunity for noninvasive control of neural activity with spatial, temporal, and cell-type specificity. These aspects were recently combined in a technique called acoustically targeted chemogenetics (ATAC) (115), which uses FUS-BBBO to deliver viral vectors to specific brain regions, using cell-specific promoters to target selected populations of cells within those regions and encoding chemogenetic receptors—proteins that respond exclusively to bioinert drugs (116)—to gain temporal control of the targeted cells. ATAC holds significant advantages over typical neuropsychiatric drugs, which act indiscriminately throughout the brain with limited regional and cellular specificity.…”
Section: Ultrasound-assisted Biomolecular Transportmentioning
confidence: 99%
“…Pioneering applications of this technology include the treatment of brain cancer 24 and neurodegenerative diseases. 25−27 To combine the spatial precision of ultrasound with the molecular, cell type, and temporal control provided by genetically engineered therapeutics, we recently developed an approach to noninvasive control of neural circuits called acoustically targeted chemogenetics, or ATAC 28 (Figure 2A, B). This technology uses FUS-BBBO to deliver adenoassociated viral (AAV) vectors into specific brain regions ( Figure 2C).…”
Section: Transport Into the Central Nervous Systemmentioning
confidence: 99%
“…treatment and a several-week period to attain robust expression of the chemogenetic receptor that lasts for at least several months. 28 Subsequently, the transfected neurons are controlled on-demand via the simple systemic administration of the chemogenetic ligand.…”
Section: Transport Into the Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Szablowski et al (2018) in a recent preprint showed that application of FUS allowed infection and expression of DREADDs in hippocampus of mice. Expression was limited to hippocampus and highly specific for excitatory neurons.…”
Section: Efficacy Of Fus For Modulating Neural Activity Perception mentioning
confidence: 99%